Use of capture-based next-generation sequencing to detect ALK fusion in plasma cell-free DNA of patients with non-small-cell lung cancer - Cui, Shaohua (Oncotarget, 2016)
Capture-based next-generation sequencing (NGS) is a potentially useful diagnostic method to measure tumor tissue DNA in blood as it can identify concordant mutations between cell-free DNA (cfDNA) and primary tumor DNA in lung cancer patients. In this study, the sensitivity, specificity and accuracy of capture-based NGS for detecting ALK fusion in plasma cfDNA was assessed. 24 patients with tissue ALK-positivity and 15 who did not harbor ALK fusion were enrolled. 13 ALK-positive samples were identified by capture-based NGS among the 24 samples with tissue ALK-positivity. In addition to EML4-ALK, 2 rare fusion types (FAM179A-ALK and COL25A1-ALK) were also identified. The overall sensitivity, specificity and accuracy for all cases were 54.2%, 100% and 71.8%, respectively. For patients without distant metastasis (M0-M1a) and patients with distant metastasis (M1b), the sensitivities were 28.6% and 64.7%, respectively. In the 15 patients who received crizotinib, the estimated median PFS was 9.93 months. Thus, captured-based NGS has acceptable sensitivity and excellent specificity for the detection of ALK fusion in plasma cfDNA, especially for patients with distant metastasis. This non-invasive method is clinically feasible for detecting ALK fusion in patients with advanced-stage NSCLC who cannot undergo traumatic examinations or have insufficient tissue samples for molecular tests.